2021
DOI: 10.3390/nu13020627
|View full text |Cite
|
Sign up to set email alerts
|

The Christian Orthodox Church Fasting Diet Is Associated with Lower Levels of Depression and Anxiety and a Better Cognitive Performance in Middle Life

Abstract: Lifestyle choices significantly influence mental health in later life. In this study we investigated the effects of the Christian Orthodox Church (COC) fasting diet, which includes long-term regular abstinence from animal-based products for half the calendar year, on cognitive function and emotional wellbeing of healthy adults. Two groups of fasting and non-fasting individuals were evaluated regarding their cognitive performance and the presence of anxiety and depression using the Mini Mental Examination Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Such a nutrient composition makes the diet enriched in fibers and folates while the amount of saturated fatty acids is significantly lowered (Rodopaios et al, 2019). Spanaki et al (2021) evaluated the cognitive profile of people following the COC fasting diet vs a group not adhering to it. The authors reported decreased levels of anxiety and depression and better cognitive performances in the COC fasting diet group.…”
Section: Diet and Brain Function Of Healthy Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a nutrient composition makes the diet enriched in fibers and folates while the amount of saturated fatty acids is significantly lowered (Rodopaios et al, 2019). Spanaki et al (2021) evaluated the cognitive profile of people following the COC fasting diet vs a group not adhering to it. The authors reported decreased levels of anxiety and depression and better cognitive performances in the COC fasting diet group.…”
Section: Diet and Brain Function Of Healthy Populationsmentioning
confidence: 99%
“…Intermittent fasting has been described for its potent impact on metabolic improvements and global health benefits (Mattson et al, 2017(Mattson et al, , 2018Mattson, 2019). The study of Spanaki et al (2021) on COC fasting diet resumes the intermittent fasting benefits while also providing evidence for a cognitive improvement even in healthy people.…”
Section: Diet and Brain Function Of Healthy Populationsmentioning
confidence: 99%
“…An interesting finding of the present study is that Orthodox fasters continued to improve their irisin status, even after the end of fasting and up to the end of the follow-up period, despite adopting their standard eating habits after week 7. Previous research has associated the adoption of OF with improved life satisfaction and wellbeing [36] and decreased prevalence of depression and anxiety [37]. Thus, we speculate that for the above-mentioned reasons, in conjunction with their strong religious beliefs, some of the participants in the OF group preferred not to entirely abandon OF and incorporated elements of this diet into their habitual nutritional plans even during the non-fasting period.…”
Section: Discussionmentioning
confidence: 83%
“…The effect of COC fasting on cognitive function and emotional wellbeing of healthy adults was evaluated by Spanki et al ( 161 ). Two groups of fasting ( n = 105) and non-fasting ( n = 107) individuals were evaluated regarding their cognitive performance using the Mini Mental Examination Scale and the presence of anxiety and depression using, the Hamilton Anxiety Scale, and the Geriatric Depression Scale, respectively.…”
Section: Greek Orthodox Christian Fastingmentioning
confidence: 99%